POLITICAL AND SOCIAL THOUGHT OF MILUTIN NEŠIĆ - Nadoveza, Branko (Political Review, 2024)
Milutin Nešić left many brochures, studies and articles in political science, often on the border between journalism and science. He wrote about classical political topics, political systems, and government. Then he wrote about the character of the new Yugoslav state after the Great War, Serbian-Croatian, Serbian-Bulgarian and Serbian-Montenegrian relations. He was a supporter of the Obrenović dynasty, he especially appreciated Prince Miloš and Prince Mihailo. He was an opponent of radicals. He believed that everything positive and useful from the West must be brought into the Serbian spirit, without jeopardizing the Serbian personality. He observes that the Serbian state was difficult to create but also difficult to build, corruption and immorality are the most dangerous among Serbian politicians.